IMPROVING ANATASE TO RUTILE TRANSITION TEMPERATURE BY MILLING - Suminar Pratapa; Triwikantoro Triwikantoro; Hariyati Purwaningsih (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2006)
IMPROVING ANATASE TO RUTILE TRANSITION TEMPERATURE BY MILLING. An intensive investigation using X-ray diffractometry has been conducted to study the optimum mechanical and thermal conditions for the transition of anatase-to-rutile from a titanium dioxide (TiO2) powder. Milling was applied by employing a conventional ball milling instrument and a quasi-high-energy pulveriser and varying the milling period. Heat treatment was performed by calcination at 850, 900, 950, 975, 1000, 1050 and 1100 °C for 1 hour, being the predicted optimum temperature to obtain fully rutile powder was 975°C. Each powder was milled and then calcined prior to the X-ray diffraction investigation. X-ray diffraction data were analysed using (1) standard identification and peak characterisation, (2) the Rietveld method to give the weight fractions, lattice constants and crystallite size and strain estimates, and (3 )Mozaix, an own-developed software to provide strain, crystallite size and size distribution of phases. Results showed that milling speed and milling up to 24 hours does not significantly change the phases’ composition, but enhances the transition temperature. Conventional milling gives better results than pulverising. Conventional milling at 100 rpm for 3 hours reduces the transition temperature from 1100°C to 1000°C. Longer milling, however, does not improve the transition temperature. The optimum process is discussed and SEM micrographs are used to support the argument.